Forgotten Citizens Deportation, Children, and the Making of American Exiles and Orphans - Zayas, Luis (Oxford University Press, 2015)
The United States Constitution insures that all persons born in the US are citizens with equal protection under the law. But in today's America, the US-born children of undocumented immigrants--over four million of them--do not enjoy fully the benefits of citizenship or of feeling that they belong. Children in mixed-status families are forgotten in the loud and discordant immigration debate. They live under the constant threat that their parents will suddenly be deported. Their parents face impossible decisions: make their children exiles or make them orphans. In Forgotten Citizens, Luis Zayas holds a mirror to a nation in crisis, providing invaluable perspectives for anyone brave enough to look. Zayas draws on his extensive work as a mental health clinician and researcher to present the most complete picture yet of how immigration policy subverts children's rights, harms their mental health, and leaves lasting psychological trauma. We meet Virginia, a kindergartener so terrified of revealing her family's status that she took her father's warning don't say anything so literally she hadn't spoken in school in over a year. We hear from Brandon, exiled with his family to Mexico, who worries that his father will die in the desert trying to immigrate again. Children like Virginia and Brandon have been silenced and their stories largely overlooked in the broader debates about immigration policy. As this book demonstrates, we can no longer afford to ignore them